Visceral Leishmaniasis in Non-Endemic Districts of Bangladesh: Knowledge gap, Attitude and Practice of Inhabitants and Professionals for Treatment, Prevention and Control (Bangladesh Journal of Zoology, 2016)
Investigation on knowledge, attitude and practice (KAP) of inhabitants and professionals for treatment, prevention and control of visceral leishmaniasis carried out on 519 inhabitants and 92 professionals of 6 districts (Panchagarh, Thakurgaon, Dinajpur, Bogra, Pabna and Shirajgonj) of Bangladesh. About 79.2% inhabitants agreed that they have heard about kala-azar disease. Regarding the transmission of kala-azar, 22.7% respondents answered by mosquito, about 38.3% said long period and irregular fever, 7.5% inhabitants knew enlargement of spleen and liver as sign and symptom of kala-azar. Among the professionals, about 80.4% of them have the correct knowledge regarding the specific agent (Leishmania donovani) of kala-azar. Investigation on knowledge, attitude and practice (KAP) of inhabitants and professional, 89.1% and 69.6% believe that spleen and liver are affected in kala-azar, 39.1% to 51.1% professionals understand that lymph nodes, blood and skin are involved as tissues due to kala-azar. Among the professionals, about 80.4% of them have the correct knowledge regarding the specific agent (L. donovani) of kala-azar.Bangladesh J. Zool. 43(2): 189-199, 2015